Flow cytometry TUNEL standardization for assaying sperm DNA fragmentation - Curi, Susana M. (2012)
We read with great interest Muratori's paper (Muratori et al, 2010), because we believe that terminal deoxynucleotidyl transferase–mediated dUTP nick end labeling (TUNEL) assay standardization is a matter of great concern and that there are certain steps that must be followed to achieve accurate results.